2018
DOI: 10.1016/j.bbadis.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific effects of apolipoprotein E expression on diet-induced obesity and white adipose tissue metabolic activation

Abstract: Apolipoprotein E (APOE) has been strongly implicated in the development of diet induced obesity. In the present study, we investigated the contribution of brain and peripherally expressed human apolipoprotein E3 (APOE3), the most common human isoform, to diet induced obesity. In our studies APOE3 knock-in (Apoe3), Apoe-deficient (apoe) and brain-specific expressing APOE3 (Apoe3) mice were fed western-type diet for 12week and biochemical analyses were performed. Moreover, AAV-mediated gene transfer of APOE3 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
9
0
4
Order By: Relevance
“…In agreement with our results, a very elegant study employing conditional apoe deletion mouse models showed that deletion of WAT-expressed apoe had no effect on morbid obesity while deletion of hepatically-expressed apoe resulted in rather higher adipocity in mice [ 66 ] , confirming the protective role of hepatically expressed APOE3 in obesity that we identified in our recently published work [ 57 ] . Therefore, the increased peripheral APOE levels observed in bariatric subjects prior to surgery [ 45 ] may not represent a cause of morbid obesity but rather a protective mechanism triggered in response to nutrient surplus, aiming at promoting excess substrate oxidation in WAT mitochondria for energy production via non-shivering thermogenesis.…”
Section: Apolipoprotein E (Apoe) In Morbid Obesity a Paradigm Shiftsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with our results, a very elegant study employing conditional apoe deletion mouse models showed that deletion of WAT-expressed apoe had no effect on morbid obesity while deletion of hepatically-expressed apoe resulted in rather higher adipocity in mice [ 66 ] , confirming the protective role of hepatically expressed APOE3 in obesity that we identified in our recently published work [ 57 ] . Therefore, the increased peripheral APOE levels observed in bariatric subjects prior to surgery [ 45 ] may not represent a cause of morbid obesity but rather a protective mechanism triggered in response to nutrient surplus, aiming at promoting excess substrate oxidation in WAT mitochondria for energy production via non-shivering thermogenesis.…”
Section: Apolipoprotein E (Apoe) In Morbid Obesity a Paradigm Shiftsupporting
confidence: 92%
“…Similarly, despite reports suggesting that adipose tissue Lrp1 may be implicated in diet-induced obesity [ 54 ] , more recent work showed that in the aP2- cre mouse, significant Cre activity is also found in ganglia of the peripheral nervous system (PNS), in adrenal medulla and in neurons throughout the CNS, proving that the aP2- cre mouse should no longer be used as a tool for adipose-tissue specific inactivation of genes [ 55 – 56 ] . Combining this information, along with our recent data showing that APOE promotes diet-induced obesity independent of its ability to mediate direct peripheral post-prandial lipid delivery to WAT [ 57 ] , an alternative interpretation of the data of Hofmann et al . [ 54 ] is that the obesity resistant phenotype of floxed- lrp1 mice crossed with aP2- cre mice is due to Lrp1 inactivation in PNS and CNS and not in adipose tissue, as originally suggested [ 54 ] .…”
Section: Apolipoprotein E (Apoe) In Morbid Obesity a Paradigm Shiftmentioning
confidence: 54%
See 1 more Smart Citation
“…In the next section, we will briefly describe genes associated with NDgD as AD, PD, and HD that were discovered by a GWAS approach and meta-analysis ( Qi et al, 2012b ; Moss et al, 2017 ; Chang et al, 2018 ; Jansen et al, 2019 ) and that had previously shown strong association with monogenic or polygenic obesity ( Tong, 2011 ; Hatziri et al, 2018 ; Wang et al, 2018a , b ; Liu et al, 2019 ). Some of the genes mentioned below are APOE and TREM2 associated with AD; CD38 variants with AD and PD; and SYT4 with PD ( Chang et al, 2018 ; Jansen et al, 2019 ).…”
Section: Genes Associated With Obesity and Neurodegenerative And Neurmentioning
confidence: 99%
“…Increasing evidence supports that the lipid and lipoprotein transport systems play a major role in the development of morbid obesity, being responsible for the management of exogenously acquired (dietary) and endogenously synthesized lipids. Among other factors, APOA1, the most abundant protein component of HDL and ApoE, a protein component of HDL/ LDL/VLDL and the functional ligand of LDLR in the clearance of TRLs from the circulation, are also major contributors to diet-induced obesity (103)(104)(105)(106)(107)(108)(109)(110). Therefore, it is conceivable to hypothesize that APOA1 and ApoE influence the processes associated with the development and progression of MM.…”
Section: Multiple Myeloma and Obesity: The Role Of Lipoproteinsmentioning
confidence: 99%